Negative Binomial Logistic Distribution - et. al., Ravikumar K, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
A new family of distributions via, Binomial Logistic Distribution (NBLD) is introduced. The various characteristics of the distribution are derived. The structural analysis of the distribution includes moments, mode, skewness, kurtosis, hazard rate. Also describes the quantile method of estimation, likelihood method of estimation, order statistics and stochastic orders. The goodness of the distribution is tested with a real data.